Effect of Pr-doping on structural, electrical, thermodynamic, and mechanical properties of BaCeO3-d as proton conductor - Basbus, Juan Felipe; Moreno Gomez, Mario Fredy; Caneiro, Alberto; Mogni, Liliana Verónica (Electrochemical Society, 2014)
Fil: Basbus, Juan Felipe. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Comisión Nacional de Energía Atómica. Centro Atómico Bariloche; Argentina